(untitled) (Research, Society and Development, 2021)
It is known that breastfeeding is extremely important because of the numerous benefits it brings to the baby. Taking into account that nipple trauma is a common reason for cessation of breastfeeding, there is a need to analyze the effectiveness and cure of this trauma with the use of laser therapy, as this method indicates a chance of decreasing breastfeeding cessation. Thus, the primary objective was to evaluate the use of laser as a means of treatment for closing breast injuries in postpartum women. This study is an experimental field research, with a descriptive quantitative approach. It was held in the city of Piripiri – PI with a total of 4 postpartum women divided into Laser Group and Orienteering Group. Nipple fissure was the main difficulty presented by the participating postpartum women. Regarding the comparison of intervention days from one group to another, the Laser Group had, on average, only 3.5 ± days of care for the healing of the nipple fissures and with a percentage variation of 75% to 80% and regarding the The Guidance Group had an average of 5± days for this healing to occur on the nipples of the mothers and with a percentage variation from 80% to 93%, taking a longer period of time for this healing to occur. Laser therapy was shown to be a safe and effective means of intervention to accelerate the healing process of breast fissures and, thus, a means of prolonging breastfeeding.